Investigation of umbilical cord serum miRNAs associated with childhood obesity: A pilot study from a birth cohort study. Issue 10 (17th June 2022) - Takatani, Rieko; Yoshioka, Yusuke; Takahashi, Tomoko; Watanabe, Masahiro; Hisada, Aya; Yamamoto, Midori; Sakurai, Kenichi; Takatani, Tomozumi; Shimojo, Naoki; Hamada, Hiromichi; Ochiya, Takahiro; Mori, Chisato
Abstract: We investigated umbilical cord serum microRNA (miRNA) profiles to identify biomarkers of a risk for obesity later in life. Participating children were divided into high‐ and low‐risk groups of obesity based on the timing of adiposity rebound and the body mass index (BMI) at 5 years and randomly selected from each group for this study. 3D‐Gene® Human miRNA Oligo Chip was performed using cord serum in five children of both groups. The most relevant miRNAs were confirmed in 33 children of the groups using the TaqMan® microRNA assay. We detected five cord serum miRNAs differentially expressed in children at high risk of obesity compared with the levels in children at low risk, namely, miR‐516‐3p and miR‐130a‐3p with increased levels and miR‐1260b, miR‐4709‐3p, and miR194‐3p with decreased levels. This study provides the first identification of altered umbilical cord serum miRNAs in childhood obesity. Abstract : This study profiled the miRNAs in cord blood and analyzed their predictive those at high and low risk of obesity, as determined using the timing of adiposity rebound and BMI at age 5. Five miRNAs that were differentially expressed in the two groups.